On unicyclic graphs of metric dimension 2 with vertices of degree 4 - Dudenko, M.; Oliynyk, B. (Algebra and Discrete Mathematics, 2018)
We show that if G is a unicyclic graph with metric dimension 2 and {a, b} is a metric basis of G then the degree of any vertex v of G is at most 4 and degrees of both a and b are at most 2. The constructions of unispider and semiunispider graphs and their knittings are introduced. Using these constructions all unicyclic graphs of metric dimension 2 with vertices of degree 4 are characterized.